X+(x+6)=33

Simple and best practice solution for X+(x+6)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x+6)=33 equation:


Simplifying
X + (x + 6) = 33

Reorder the terms:
X + (6 + x) = 33

Remove parenthesis around (6 + x)
X + 6 + x = 33

Reorder the terms:
6 + X + x = 33

Solving
6 + X + x = 33

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + X + -6 + x = 33 + -6

Reorder the terms:
6 + -6 + X + x = 33 + -6

Combine like terms: 6 + -6 = 0
0 + X + x = 33 + -6
X + x = 33 + -6

Combine like terms: 33 + -6 = 27
X + x = 27

Add '-1x' to each side of the equation.
X + x + -1x = 27 + -1x

Combine like terms: x + -1x = 0
X + 0 = 27 + -1x
X = 27 + -1x

Simplifying
X = 27 + -1x

See similar equations:

| 10x=-52 | | (y-1)(y-1)=2y^2+6y+16 | | ((2/3)a)+2=((1/3)(4a+1)) | | 2w^2-14w+33=(w-6)(w-6) | | y^2+17y=72-0 | | 3(x-2)/2=-3x | | 10x=52 | | I=300*.11*2 | | 70x+10y=100 | | 3/4x+y=4 | | x^2-13x+6.5=0 | | -20x=4x^2+25 | | 2t^2+7t-4=0 | | (2/3)a+2=(1/3)(4a+1) | | -x-(2/5)=x+(1/2)+(1/5) | | y=-10+10 | | 75-(-10)= | | 5p-3=12p+11 | | 1/3d=60 | | 5u^2+20u=0 | | 12+.45x=20 | | 6w^2-12w=0 | | 8.4+6.7*8/8 | | 6h=358 | | 4y^2=-20y | | 3ln(7x)=12 | | 6(-7/18p)+2p | | -6(v+9)=6v-18 | | 2x-(-4)=2 | | -8x^4+72x^5/12x^5 | | 27r+55=190 | | p=2(2)+2(89) |

Equations solver categories